THE USE OF KINESITHERAPY ACCORDING TO THE NEURAK SYSTEMA IN RADICULOPATHY - Зендик, Алёна; Ротарь, Яна (SWorldJournal, 2021)
In the article the presented review of publications that touch the problems of physical rehabilitation of patients with the diagnosis of radiculopathy with application of the newest technology of employments on the system Neurak . For today about such con